China’s soft power conundrum - How film coproduction functions - Keane, Michael; Peng, W. (Sage Publications Ltd., 2018)
China’s soft power push and its effectiveness, or lack thereof relative to its success in economic and military growth, has received considerable journalistic and academic attention both inside and outside China. This paper looks at China’s soft power strategy in relation to the film industry, which since the early 2000s has opened to international co-productions and investment. With an investigation of film’s role in promoting soft power, it asks how the film coproduction strategy might play out in an era of increased nationalism. In addition, the paper pays attention to the institutional problem- the tension between artistic freedom and censorship that challenges coproduction and undermines the efficacy of China’s soft power strategy.